Profitability, Liquidity, and Financial Performance: Implications for Company Value in Indonesia’s Mining Industry - Ariawan, Ariawan (International Journal of Business, Law, and Education, 2023)
This research explores the interplay between profitability, liquidity, financial performance, and company value in Indonesia's mining industry. quantitative approach is employed, utilizing path analysis to examine complex relationships and understand how these variables collectively influence the mining companies' value in Indonesia. The study targets 40 mining companies from a population of 73, using purposive sampling based on the completeness of financial statements from 2018 to 2022.Results from the path analysis are discussed, revealing positive and significant effects of liquidity on financial performance and company value. Profitability also demonstrates a positive impact on both financial performance and company value. The findings align with previous research and contribute to a comprehensive understanding of the financial landscape of Indonesia's mining industry. The study's implications extend to investors, companies, and regulatory policies, emphasizing the importance of considering liquidity and profitability in strategic planning and decision-making. In conclusion, the research provides valuable insights for stakeholders in the Indonesian mining industry, emphasizing the interconnectedness of liquidity, profitability, financial performance, and company value. These findings contribute to informed decision-making and risk management in the dynamic and volatile environment of the mining sector.